Regulatory roles of miRNAs in development and progression of Hepatocellular carcinoma - Yasmeen Ishaq; Bisma Rauff; Muhammad Rehan Chaudhry; Mohamad S. Hakim; Sana Khurshid; Shafiq Ahmad Chudhary; Aqsa Ikram (Molecular Biology Reports, 2026)

Multiplex CRISPR/Cas9 editing of gliotoxin biosynthesis genes in Aspergillus fumigatus reduces pathogenicity in broilers - Mishal Khalid; Aamna Ishaq; Mahreen Arshad; Haiba Kaul; Muhammad Majeed (Brazilian Journal of Microbiology, 2026)

A Systematic review on sago starch-based bioplastics: Modification techniques, properties, and sustainability potentials - Muhammad Iskandar Ishaq; Muhammad Abdillah Hasan Qonit; I Gusti Komang Dana Arsana; Saptowo Jumali Pardal; Muhammad Ace Suhendar; Abdul Azis; Idawanni; Syariful Mubarok; Muhammad Luthfan Haziman (Next Research, 2026)

Experimental and numerical investigation of cleaning performance of obliquely impinging cavitating jets for barnacle removal from hull surfaces - Xiaohui Zhang; Haonan Ji; Shize Pan; Haitao Zhu; Muhammad Ishaq; Zhongliang Xie; Xiaosong Zhang; Chuntong Li (Ocean Engineering, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Lactiplantibacillus plantarum AS21 Reduces Colitis in Mice by Modulating Inflammation, Gut Barrier Function, and Microbiota in an Intervention Dose and Time-dependent Manner - Ali Sher Bacha; Mengyan Chen; Zitong Ding; Mengya Jia; Hu Chen; Ikram Khan; Muhammad Ishaq; Azmat Ullah Jan; Ashiq Khan; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

A New Species of Coprinellus (Psathyrellaceae, Agaricales) From Buner District, Pakistan - Muhammad Ishaq; Sana; Muhammad Binyamin Khan; Munazza Kiran; Muhammad Fiaz; Abdul Nasir Khalid; Ting Chi Wen (New Zealand Journal of Botany, 2026)
A new species, Coprinellus nigrolamellatus , is described hereby from the Buner District, Khyber Pakhtunkhwa Province, Pakistan. The species is distinguished based on both morphological features and molecular data, with nrITS sequences confirming its unique status. Coprinellus nigrolamellatus is characterized by small‐ to medium‐sized basidiomata; an applanate and grayish‐brown pileus with yellowish orange central disk; adnexed, slowly deliquescent, and black lamellae; mitriform basidiospores (in front view) distinctly flattened (in side view) with a central germ pore; clavate to broadly clavate cheilocystidia; irregularly cylindrical pileocystidia; thick‐walled and globose to subcylindrical veil elements; and the absence of pleurocystidia. Phylogenetically, it forms a well‐supported sister clade to Coprinellus verrucispermus within section Coprinellus . Descriptions, illustrations, phylogenetic analysis results, and comparisons with closely related taxa are provided for the studied species.

Robust Adaptive Propagated Interval Observer for Actuator Fault Diagnosis in Underactuated AUVs - Ishaq Ahmed; Ayman Alharbi; Jun Lu; Amar Jaffar; Muhammad Bilal (Journal of Marine Science and Engineering, 2026)
This paper presents an interval-observer-based actuator fault detection and isolation (FDI) method for underactuated autonomous underwater vehicles (AUVs) under bounded hydrodynamic uncertainty and time-varying ocean currents. A locally frozen linear time-invariant (LTI) representation enables deterministic set-membership analysis, and the robust adaptive propagated interval observer (RAPIO) propagates admissible center–radius state bounds within a Lyapunov framework. Adaptivity is introduced through a reinforcement learning (RL)-augmented uncertainty-bound modulation mechanism, where an offline-trained agent scales a nonnegative channel-wise slack term without modifying the scheduled observer-gain rule or the nominal center predictor. Under the stated observer and disturbance-envelope conditions, positivity, stability, and diagnostic-channel inclusion hold for any bounded learning signal. Actuator loss-of-effectiveness (LoE) faults are represented through the actuator-effectiveness channel and detected through interval-consistency violations, enabling axis-wise isolation of surge, yaw-rate, and pitch-rate actuator faults. The same schedule-blind decision layer is additionally evaluated with structurally distinct additive-bias and stuck/jam actuator models. All stuck/jam events are detected, and bias-magnitude sweeps identify channel-wise 100%-detection boundaries with zero false alarms. A structured 72-case scenario sweep shows reliable detection, strong false-alarm rejection, and acceptable detection delays compared with benchmark observers.

Metagenomic surveillance identifies a high-risk antibiotic resistance profile in community wastewater: a pilot study from Pakistan - Ishaq Khan; Ihtisham Naeem; Shujait Ali; Mahnoor Gulbin; Arshad Iqbal; Muhammad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correction: Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2026)

Integrative reverse vaccinology and computational modeling for the rational design of a broadly immunogenic multi-epitope vaccine against Marburg virus infection - Asadullah Khan; Sitara Bibi; Li Pinyi; Khalida Latif; Muhammad Rahiyab; Ishaq Khan; Arshad Iqbal; Itazaz Ul Haq; Syed Shujait Ali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Erratum to: Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Zircon U-Pb, Hf isotope and trace element geochemistry from the newly found Neoproterozoic granitoids in Wadh-Khuzdar area, Balochistan, Pakistan: constraints on magma genesis and tectonic settings - Muhammad Hussain; Hafiz U. Rehman; Muhammad Ishaq Kakar; Hao-Yang Lee; Sun-Lin Chung; Kaushik Das; Mehboob ur Rashid; Nasir Ahmad; Tehseen Zafar; Hiroshi Yamamoto (Precambrian Research, 2026)

Protective effects of zinc and Prunus amygdalus against cadmium-induced nephrotoxicity in male Albino rats - Muhammad Talha Ishaq; Faiza Zubair; Naila Riaz; Hira Kanwal; Ayesha Tehreem Shahbaz; Tooba Tahir; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Journal of Trace Elements in Medicine and Biology, 2026)

Peroxide crosslinking of UHMWPE using tea-polyphenols as anti-oxidants - Muhammad Aaqib Ishaq; Muhammad Kaleem Ullah Khalil; Qazi Muhammad Yaseen; Mohsin Hayat (Next Research, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Combined effect of different calcination temperatures and non-equilibrium low-pressure plasma on photocatalytic activity of bi-phasic heterostructured CuMoO4-ZrO2/GO composite - Mahwish Iqbal; Tehmeena Ishaq; Muhammad Ahsan Rashid; Mahreen Iqbal; Haq Nawaz Bhatti (Journal of Water Process Engineering, 2026)

Detection and serotyping of bluetongue viruses in Khyber Pakhtunkhwa Province, Pakistan - Muhammad Ishaq; Syed M. Jamal; Syed Asad Ali Shah; Hanif Ur Rahman; Alessandra Leone; Liana Teodori; Maura Pisciella; Ottavio Portanti; Cesare Cammà; Valentina Curini; Maurilia Marcacci; Barbara Secondini; et al. (Tropical Animal Health and Production, 2026)

Morphological Studies and Phylogenetic Analysis Unveil a New Species of Russula Subg. Heterophyllinae (Russulaceae, Russulales) from Pakistan - Muhammad Fiaz; Sana; Muhammad Binyamin Khan; Munazza Kiran; Muhammad Ishaq; Abdul Nasir Khalid; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Russula subg. Heterophyllidiae is both ecologically and economically important. In the present study, a new Russula species, R . pakistanica , is described from Mansehra District, Khyber Pakhtunkhwa Province, Pakistan, based on morphology and molecular phylogenetic analyses of internal transcribed spacer (nrITS) region. Both morphological and phylogenetic analyses consistently confirmed that the species described belongs to Russula subg. Heterophyllidiae subsect. Virescentinae . Russula pakistanica is characterized by a concave, centrally depressed, striated, and light gray to cream yellow pileus; narrowly adnate and pale olive‐gray lamellae; clavate and very light gray to creamy buff stipe with bulbous base; broadly ellipsoid and partially reticulated basidiospores (average 8.5 × 6.6 μm); clavate to fusoid hymenial cystidia with obtuse apices; and the absence of marginal cells and pileocystidia. Phylogenetically, it formed a distinct and well‐supported sister clade to Chinese R . pallidula . The new species’ description, illustrations, phylogenetic analyses results, and comparison with closely related taxa are provided in this article.

Hydrogen production from hydrogen sulfide via a uniquely designed electrolysis process: experimental investigation - Muhammad Ishaq; Ibrahim Dincer (Fuel, 2026)

Repurposing fluoroquinolones as cancer chemosensitizers: a way to overcome cancer therapeutic bottleneck - Muhammad Ishaq; Erum Zafar; Muhammad Faisal Maqbool; Muhammad Mansha; Muhammad Khan; Yongming Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Fungal endophytes isolated from Withania somnifera Markedly exhibit antitumor activity against human glioblastoma - Arshad Ahmad; Sumera Afzal Khan; Ishaq Nasib Khan; Amjad Iqbal; Muhammad Hamayun (Natural Product Research, 2025)

Investigating the taxonomic scope of Meliolales species–host relationships and geographic trend - Muhammad Binyamin Khan; Abdul Wahab; Sana; Sardar Ali; De-Ping Wei; Marasinghe Wadige Diana Sandamali; S. Hongsanan; Xiang-Yu Zeng; Muhammad Ishaq; Munazza Kiran; Ting Chi Wen (New Zealand Journal of Botany, 2025)

Experimental design and evaluation of a thermoelectric cold storage system - Faiq Said; Muhammad Aaqib Ishaq; Muhammad Arsalan Khan; Hafiz Basit Ali (Next Research, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Optimizing Charge Transport Properties of Dithieno[3,2-b:2′,3′-d] Pyrrole-Based Hole Transport Materials for Perovskite Solar Cells: a DFT Study - Nabeel Shahzad; Muhammad Ishaq; Aqsa Laraib; Tazeem Fatima; Rida Fatima; Waqas Akram; Javed Iqbal (Journal of Fluorescence, 2025)

An innovative integrated system developed for hydrogen fuel production and sulfur recovery from acid gas streams for sustainable development - Muhammad Ishaq; Ibrahim Dincer (Journal of Environmental Chemical Engineering, 2025)

Restoration of alkaline soils contaminated by inorganic elements under pulsed electrokinetics - Abdul Ahad Hussain; Muhammad Moeez; Aasma Akram; Mubashera Ishaq; Kashif Kamran; Muhammad Afzaal; Maryam Hina; Lin Li (Environmental Research, 2025)

A systematic review on the development and efficacy of nano-based vaccine in aquaculture - Shamsu Ibrahim Ishaq; Muhammad Salahudin Kheirel Anuar; Abdulwakil Olawale Saba; Ina Salwany Md Yasin; Che Azurahanim Che Abdullah; Annas Salleh; Muhammad Farhan Nazarudin; Mohd Termizi Yusof; Mohammad Noor Amal Azmai (Aquaculture International, 2025)

Using immunoinformatics and bioinformatics approach to design novel and effective rational in-silico vaccine against human Astrovirus targeting the capsid polyprotein VP90: a silent threat to global gastrointestinal tract - Itazaz Ul Haq; Najeeb Ullah; Muhammad Rahiyab; Ruqia Sartaj; Ishaq Khan; Syed Shujait Ali; Fazal Akbar; Arshad Iqbal (In Silico Pharmacology, 2025)

Evaluation of testicular protective effects of Prunus amygdalus and zinc against cadmium induced toxicity in rats - Ayesha Tehreem Shahbaz; Faiza Zubair; Naila Riaz; Hira Kanwal; Tooba Tahir; Muhammad Talha Ishaq; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Environmental Science and Pollution Research, 2025)

Dynamic modeling and optimal control schemes for an offshore-wind powered direct air capture system with energy storage options - Muhammad Faisal Shehzad; Haris Ishaq; Curran Crawfrod (Science of The Total Environment, 2025)

GC–MS Profiling and Computational Analysis of Potato Peel Extracts Reveal Promising Avenue of Novel Therapeutic Potential: An Embarking Step towards Drugs Design - Iqra Sarwar; Farhat Yasmeen; Muhammad Iqbal; Muhammad Atif; Muhammad Ishaq; Zeenat Haq; Sabahat Javid; Anam Liaqat (Potato Research, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Organic matter enrichment and shale-oil bearing reservoir potential of the inter-salt shales in the eocene Bahadur Khel salt from the Kohat basin, North Pakistan - Muhammad Ishaq; Muhammad Hanif; Mohammed Hail Hakimi; Muhammad Rizwan; Samina Jahandad; Afikah Rahim; Ali Y. Kahal (Carbonates and Evaporites, 2025)

How shallow solum shapes plant selection, tree diversity, carbon stocks and earthworms in coffee agroforestry - Rika Ratna Sari; Muhammad Naufal Ramadhan; Nadiyah Rifdatun Nailah; Nanda Ardiansyah; Ahmad Ali Yuddin Fitra; Arif Firmansyah; Rizki Maulana Ishaq; Danny Dwi Saputra (Agroforestry Systems, 2025)

Omics Technologies: Unraveling Abiotic Stress Tolerance Mechanisms for Sustainable Crop Improvement - Muhammad Hamzah Saleem; Sana Noreen; Izwa Ishaq; Ammara Saleem; Khalid Ali Khan; Sezai Ercisli; Muhammad Anas; Awais Khalid; Temoor Ahmed; Ammara Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Talaromyces purpureogenus-mediated mycosynthesis of aluminium oxide nanoparticles and characterization of the physicochemical properties at different calcination temperatures - Muhammad Salahudin Kheirel Anuar; Che Azurahanim Che Abdullah; Muhammad Farhan Nazarudin; Shamsu Ibrahim Ishaq; Mohammad Noor Amal Azmai; Annas Salleh; Ina Salwany Md Yasin; Mohd Termizi Yusof (Fungal Biology, 2025)

Inferring paleoenvironmental changes from integrated facies analysis of the late Paleocene-early Eocene succession, Salt Range, Pakistan - Muhammad Hanif; Mahnoor Sabba; Iftikhar Ahmed Abbasi; Mohamed Abioui; Nowrad Ali; Muhammad Ishaq (Carbonates and Evaporites, 2025)

Impact of petrographic and physico-mechanical properties on aggregate suitability of the early Devonian Nowshera formation: a case study from the Peshawar Basin, Pakistan - Abid Nawaz; Muhammad Sajid; Waqas Ahmed; Abdul Rahim Asif; Muhammad Ishaq (Carbonates and Evaporites, 2025)

A Potent Plant-Derived Chitinase: Structural Informatics and Insecticidal Activity against Helicoverpa armigera - Shah Rukh; Ahmed Akrem; Qamar Saeed; Sohaib Mehmood; Nosherwan Adil; Tazeen Rao; Muhammad Nasir; Uzma Ishaq; Aqal Zaman; Najeeb Ullah; Mohibullah Shah (Cell Biochemistry and Biophysics, 2025)

Nutritional profiling and selection of promising F3 sorghum genotypes from bioguma and Gando Keta crosses for food security and industrial applications - Endang Gati Lestari; Heny Herawati; Suarni Suarni; Muhammad Iskandar Ishaq; Karlina Syahruddin; Diana Widiastuti; Ade Heri Mulyati; Rossa Yunita; Muhammad Luthfan Haziman; Suparjo (Food and Humanity, 2025)

Life cycle assessment of turning hydrogen sulfide recovered from sea waters into clean hydrogen - Muhammad Ishaq; Ibrahim Dincer (Resources, Conservation and Recycling, 2025)

An improved sulfur iodine cycle for sour gas purification and hydrogen fuel production for better environment - Muhammad Ishaq; Ibrahim Dincer (Journal of Environmental Management, 2025)

Spatio-temporal analysis of PM2.5 and its association with elevation by using remote sensing: the scenario of Quetta, Pakistan - Laraib Ehtasham; Malik Muhammad Akhtar; Salman Tariq; Ishaq Ahmad Mian (Air Quality, Atmosphere & Health, 2025)

Effect of soil types and moisture contents on the pupation behavior and adult emergence of Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Muhammad Bilal; Muhammad Mamoon-ur-Rashid; Shabana Wazir; Muhammad Naeem; Asif Ishaq; Rana Muhammad Kaleem Ullah; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Theabrownin: a dietary nutraceutical with diverse anticancer mechanisms - Muhammad Faisal Maqbool; Sameena Gul; Muhammad Ishaq; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan; Yongming Li; Tonghui Ma (Natural Product Research, 2025)

Marine actinomycetes: a hidden treasure trove for antibacterial discovery - Chengqian Pan; Syed Shams ul Hassan; Muhammad Ishaq; Shikai Yan; Huizi Jin (Frontiers in Marine Science, 2025)
Oceans boast a substantial microbial diversity, which is widely prevalent in seawater, marine sediments, and marine organisms. In contrast to terrestrial resources explored in traditional natural product research, the habitats of marine microorganisms are distinctly unique. Actinomycetes serve as a vital source of secondary metabolites, including antibiotics and other potent natural products like streptomycin and tetracycline. They have played a pivotal role in clinical treatments for significant diseases such as pathogenic bacterial infections. Nevertheless, the extensive use of antibiotics has led to a sharp increase in the variety and number of drug-resistant bacteria, notably multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacteria, in clinical settings, posing a grave threat to human survival. Consequently, there is an immediate need to discover structurally novel antibacterial natural products and develop new antibiotics. This mini review summarizes a total of 45 novel antibacterial natural products derived from marine actinomycetes, published in 2024. These products, including polyketides, alkaloids, macrolactams, and peptides, are highlighted in terms of their structures and biological activities. The objective of this article is to provide valuable insights for the research and development of novel antibiotics.

Carbon dioxide, global boiling, and climate carnage, from generation to assimilation, photocatalytic conversion to renewable fuels, and mechanism - Muhammad Khan; Xiaohui Sun; Amir Zada; Shohreh Azizi; Muhammad Ishaq Ali Shah; Javed Ali Khan; Ahmed H. Ragab; Mostafa A. Taher; Qumber Abbas; Changseok Han (Science of The Total Environment, 2025)

Marine fungi as a goldmine for novel antibiotics: a 2024 perspective - Chengqian Pan; Syed Shams ul Hassan; Ishaq Muhammad; Huizi Jin (Frontiers in Marine Science, 2025)
The microbial diversity in oceans is considerable, widely distributed in seawater, marine sediments, and marine organisms. Compared with terrestrial resources in traditional natural product research, the living environments of marine microorganisms are starkly different. The drastic differences in survival conditions, such as high salinity, oligotrophic conditions, lack of light, and limited oxygen, determine that microorganisms exhibit distinctive characteristics in metabolism, survival modes, and adaptive mechanisms. These factors contribute to significant distinctions in secondary metabolic pathways and enzymatic reaction mechanisms between marine and terrestrial microorganisms. In this review, we summarized a total of 72 novel natural products with antibacterial activity, published in 2024, which are derived from marine-derived fungi. These products (polyketides, alkaloids, terpenoids, and peptides) are emphasized in terms of their structures and biological activities. This article aims to provide useful information for the research and development of novel antibiotics.

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Sorghum starch review: Structural properties, interactions with proteins and polyphenols, and modification of physicochemical properties - Muhammad Luthfan Haziman; Muhammad Iskandar Ishaq; Muhammad Abdillah Hasan Qonit; Endang Gati Lestari; Pepi Nur Susilawati; Wiwi Widarsih; Cheppy Syukur; Heny Herawati; Ramlah Arief; Budi Santosa; Resmayeti Purba; Robi Andoyo; et al. (Food Chemistry, 2025)

Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2024)

A new system using refuse-derived fuel as a feedstock for hydrogen and power co-generation: A techno-environmental assessment - Muhammad Ishaq; Ibrahim Dincer (Process Safety and Environmental Protection, 2024)

Evolution of the Late Cretaceous orbitoidal foraminifera and implications for the taxonomy and biostratigraphy in the Eastern Neo-Tethys, Lower Indus Basin, Pakistan: A biometric approach - Muhammad Rizwan; Muhammad Hanif; Muhammad Ishaq (Journal of Asian Earth Sciences, 2024)

An advanced design to generate power and hydrogen with CO2 capturing and storage for cleaner applications - Muhammad Ishaq; Ibrahim Dincer (Chemical Engineering Journal, 2024)

Heterojunction interface engineering enabling high transmittance and record efficiency in Sb2S3 semitransparent solar cell - Muhammad Ishaq; Xuerui Li; Safdar Mehmood; Yi-Ming Zhong; Adil Mansoor; Usman Ali Shah; Shuo Chen; Yuexing Chen; Zhuanghao Zheng; Guangxing Liang (Chemical Engineering Journal, 2024)

Notes on species of Sporisorium and Ustilago from Pakistan - Sadiq Ullah; Najam-ul-Sehar Afshan; Aamna Ishaq; Maria Riaz; Muhammad Fiaz; Abdul Nasir Khalid; Mary Catherine Aime (Mycological Progress, 2024)

Deposition and diagenesis of the Triassic-Jurassic limestone successions of the northwestern passive margin of the Indian plate, Sulaiman Fold-Thrust Belt, Pakistan - Razzaq Abdul Manan; Akhtar Muhammad Kassi; Henrik Friis; Aimal Khan Kasi; Syed Haroon Ali; Mohammad Ahmed Farooqui; Muhammad Ishaq Kakar (Carbonates and Evaporites, 2024)

A cradle-to-gate life cycle assessment for clean hydrogen gas production pathway using the CeO2/Ce2O3-based redox thermochemical cycle - Muhammad Ishaq; Ibrahim Dincer (Gas Science and Engineering, 2024)

Design and Evaluation of Inorganic/Organic Hybrid Bio-composite for Site-Specific Oral Delivery of Darifenacin - Wafa Ishaq; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz; Sherjeel Adnan; Hammad Ahmed; Muhammad Waqas; Zainab Safdar (AAPS PharmSciTech, 2024)
Benign hyperplasia (BHP) is a common disorder that affects men over the age of 60 years. Transurethral resection of the prostate (TURP) is the gold standard for operative treatment, but a range of drugs are also available to improve quality of life and to reduce BHP-associated urinary tract infections and complications. Darifenacin, an anti-muscarinic agent, has been found effective for relieving symptoms of overactive bladder associated with BHP, but the drug has poor solubility and bioavailability, which are major challenges in product development. An inorganic/organic bio-composite with gastric pH-resistant property was synthesized for the targeted oral delivery of Darifenacin to the lower gastrointestinal tract (GIT). This development was accomplished through co-precipitation of calcium carbonate in quince seed-based mucilage. The FTIR, XRD, DSC, and TGA results showed good drug-polymer compatibility, and the SEM images showed calcite formation in the quince hydrogel system. After 72 h, the drug release of 34% and 75% were observed in acidic (0.1N HCl) and 6.8 pH phosphate buffer, respectively. A restricted/less drug was permeated through gastric membrane (21.8%) as compared to permeation through intestinal membrane (65%.) The developed composite showed significant reduction in testosterone-induced prostatic hyperplasia (2.39 ± 0.12***) as compared to untreated diseased animal group. No sign of organ toxicity was observed against all the developed composites. In this study, we developed an inorganic–organic composite system that is highly biocompatible and effective for targeting the lower GIT, thereby avoiding the first-pass metabolism of darifenacin. Graphical Abstract

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Role of social networks and entrepreneurial success: Understanding the dynamics of knowledge acquisition and green entrepreneurial orientation - Saba Riaz; Wang Yanqing; Muhammad Ishtiaq Ishaq; Ali Raza; Roheel Ahmad Siddiqui (Journal of Cleaner Production, 2024)

A novel integrated gas-cooled fast nuclear reactor and vanadium chloride thermochemical cycle for sustainable fuel production - Muhammad Ishaq; Ibrahim Dincer (Journal of Cleaner Production, 2024)

Investigation of a tri-renewable energy system coupled with battery and hydrogen storages for a sustainable city - Muhammad Ishaq; Ibrahim Dincer (Sustainable Cities and Society, 2024)

Mesozoic structural evolution of the Northern South China Sea margin using potential field modelling - Syed Wajid Hanif Bukhari; Sanzhong Li; Jie Liu; Ze Liu; Muhammad Farhan; Ishaq Kakar (Tectonophysics, 2024)

Plant-mediated green synthesis of silver nanoparticles: Synthesis, characterization, biological applications, and toxicological considerations: A review - Zarfishan Zulfiqar; Rana Rashad Mahmood Khan; Muhammad Summer; Zohaib Saeed; Muhammad Pervaiz; Shahzad Rasheed; Behram Shehzad; Fatima Kabir; Saira Ishaq (Biocatalysis and Agricultural Biotechnology, 2024)

Depositional and Bio-Sequence Stratigraphic Framework of Late Cretaceous Kawagarh Formation, Kala-Chitta Range, Pakistan: Equivalent of Gurpi Formation (Iran) - Muhammad Awais; Bilal Wadood; Muhammad Ishaq; Muhammad Bilal; Zeeshan Zafar; Nasar Khan; Aminullah Khan (Journal of Earth Science, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Advances in ionic liquids as fluorescent sensors - Farva Ilyas; Hira Fazal; Muhktiar Ahmed; Asma Iqbal; Muhammad Ishaq; Maher Jabeen; Madiha Butt; Sumbal Farid (Chemosphere, 2024)

Recent advances in applications of marine hydrocolloids for improving bread quality - Anum Ishaq; Muhammad Nadeem; Rafiq Ahmad; Zahoor Ahmed; Nauman Khalid (Food Hydrocolloids, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Impacts of riverbank erosion and flooding on communities along the Indus River, Pakistan - Dilshad Ahmad; Muhammad Afzal; Muhammad Ishaq (Natural Hazards, 2024)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Spatiotemporal variation in the vegetation cover of Peshawar Basin in response to climate change - Ishaq Ali Shah; Zahir Muhammad; Haroon Khan; Rehman Ullah; Atta-ur Rahman (Environmental Monitoring and Assessment, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Sustainable assessment of an integrated energy system coupled with solar thermochemical cycle - Muhammad Ishaq; Haris Ishaq (Journal of Cleaner Production, 2023)

Geology, mineralogy, and geochemistry of Naweoba and Bagh Cyprus-type VMS deposits of the Late Cretaceous Zhob Valley Ophiolites, Pakistan: implications for genesis - Muhammad Ayoub Khan; Thomas Ulrich; Muhammad Ishaq Kakar; Mohamed Metwaly; Abdul Naeem; Shazia Fareed (Arabian Journal of Geosciences, 2023)

Prevalence and risk factors of bluetongue in small and large ruminants maintained on Government farms in North-western Pakistan - Muhammad Ishaq; Syed Asad Ali Shah; Nadar Khan; Syed M. Jamal (Research in Veterinary Science, 2023)

Usage of the XGBoost and MARS algorithms for predicting body weight in Kajli sheep breed - Asim Faraz; Cem Tırınk; Hasan Önder; Uğur Şen; Hafiz Muhammad Ishaq; Nasir Ali Tauqir; Abdul Waheed; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2023)

A causal link between financialization and ecological status: a novel framework for Asian countries? - Saeed Ahmad Sabir; Mubeen Abdur Rehman; Muhammad Zahid Javed; Usman Mehmood; Rabia Ishaq (Environmental Science and Pollution Research, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Detailed diagenetic investigation and their impact on the reservoir potential of Upper Cretaceous mixed carbonate-siliciclastic succession, Rakhi Nala Section, Eastern Sulaiman Range, Pakistan - Muhammad Rizwan; Muhammad Hanif; Shuja Ullah; Muhammad Ishaq (Carbonates and Evaporites, 2023)

Achieving business competitiveness through corporate social responsibility and dynamic capabilities: An empirical evidence from emerging economy - Huma Sarwar; Junaid Aftab; Muhammad Ishtiaq Ishaq; Muhammad Atif (Journal of Cleaner Production, 2023)

Defects passivation by solution-processed titanium doping strategy towards high efficiency kesterite solar cells - Umar Farooq; Usman Ali Shah; Muhammad Ishaq; Ju-Guang Hu; Shehzad Ahmed; Shuo Chen; Zhuang-Hao Zheng; Zheng-Hua Su; Ping Fan; Guang-Xing Liang (Chemical Engineering Journal, 2023)

Museum of Earth Sciences of the Geological Survey of Pakistan (MESGSP): a Potential Geotourism Attraction - Mukhtiar Ghani; Robert Raynolds; Rahat Ullah; Mohibullah Mohibullah; Muhammad Ishaq Kakar (Geoheritage, 2022)

Influence of HRM on CSR and performance of upscale hotels in developed and developing countries - Huma Sarwar; Muhammad Ishtiaq Ishaq; Simona Franzoni (Environment, Development and Sustainability, 2022)
The researchers showed their increased interest in linking human resource management (HRM) and corporate social responsibility (CSR) practices in recent studies. HRM is a critical factor in how CSR should be enacted, developed, and understood at a broader level to achieve organizational benefits. Hence, it is evident that current studies are asking for more studies on HRM–CSR nexus, and we argue that such a relationship is necessary and relevant. Probing more in this research stream, the current research investigates the impact of HRM and CSR on sustainable performance. More specifically, this study explores how 3-star, 4-star, and 5-star hotels achieve sustainable performance through HRM and CSR in the hospitality industry of the UK, Italy, and Pakistan. A stratified random sampling technique was used to select the hotels by collecting hotel details from Chambers of the Commerce United Kingdom, Italian Government Statistics, and Pakistan Hotel Associations for the UK, Italy, and Pakistan. Through a highly structured survey questionnaire, the data were collected from 438 UK, 520 Italian, and 354 Pakistani hotels. The results confirm the HRM–CSR–sustainable performance nexus in the hospitality industries of three countries. They show that HRM impact on CSR and sustainable performance is relatively stronger in five-star hotels followed by three-star and then four-star hotels. These results supported the resource-based view theory by providing strong evidence that HRM and CSR are essential resources for achieving sustainable performance and competitive advantage.

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

Geology and petrogenesis of gabbro from the Zhob Ophiolite, Balochistan, Pakistan - Abdul Naeem; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Andrew C. Kerr; Muhammad Qasim Jan; Muhammad Ayoub Khan (Arabian Journal of Geosciences, 2022)

Trajectory of anti-SARS-COV-2 IgG antibodies from onset of symptoms to 6 months in a cohort of Pakistani patients - Maria Mehmood; Haleema Usman Khan; Muhammad Ihtesham Khan; Ishaq Khan; Rajaa Mohammad Al-Raddadi; Steve Harakeh; Yasar Mehmood Yousafzai (Infectious Diseases, 2022)

Do Agriculture Technologies Influence Carbon Emissions in Pakistan? Evidence based on ARDL technique - Rafaqet Ali; Rabia Ishaq; Khuda Bakhsh; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2022)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Assessing the physico-chemical parameters and some metals of underground water and associated soil in the arid and semiarid regions of Tank District, Khyber Pakhtunkhwa, Pakistan - Asif Khan; Muhammad Naeem; Muhammad Bilal; Abbas Khan; Fazle Subhan; Muhammad Ikram; Muhammad Ishaq Ali Shah; Saleem Ullah; Asmat Ullah; Atta Ullah (Environmental Monitoring and Assessment, 2021)

Candidate Rlm6 resistance genes against Leptosphaeria. maculans identified through a genome-wide association study in Brassica juncea (L.) Czern - Hua Yang; Nur Shuhadah Mohd Saad; Muhammad Ishaq Ibrahim; Philipp E. Bayer; Ting Xiang Neik; Anita A. Severn-Ellis; Aneeta Pradhan; Soodeh Tirnaz; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2021)

Indoor transmission dynamics of expired SARS-CoV-2 virus in a model African hospital ward - Jamiu Adetayo Adeniran; Ishaq Alhassan Mohammed; Oladele Idris Muniru; Taofeek Oloyede; Omowonuola Olubukola Sonibare; Muhammad-Najeeb O. Yusuf; Khadijat Abdulkareem Abdulraheem; Emmanuel Tolulope Odediran; Rafiu Olasunkanmi Yusuf; Jacob Ademola Sonibare (Journal of Environmental Health Science and Engineering, 2021)

Synthesis of novel nicotinamide susbstituted phthalocyanine and photodynamic antomicrobial chemotherapy evaluation potentiated by potassium iodide against the gram positive S. aureus and gram negative E. coli - Azeem Ullah; Tingkai Zhao; Munira Taj Muhammad; Muhammad Khan; Saira Qurban; Abdul Rahman; Ishaq Ahmad (Biotechnology Letters, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Petrology and geochemistry of volcanic and volcanoclastic rocks from Zhob ophiolite, North-Western Pakistan - Abdul Naeem; Andrew C. Kerr; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Muhammad Ayoub Khan; Nisar Ahmed (Arabian Journal of Geosciences, 2021)

Three new guaiane-type sesquiterpenoids and a monoterpenoid from Litsea lancilimba Merr - Ishaq Muhammad; Yong Zhen Xiao; Syed Shams ul Hassan; Xue Xiao; Shi-Kai Yan; Yuan-Qiang Guo; Xian-peng Ma; Hui-Zi Jin (Natural Product Research, 2020)

Potentially toxic elements’ occurrence and risk assessment through water and soil of Chitral urban environment, Pakistan: a case study - Inayat ur Rehman; Muhammad Ishaq; Liaqat Ali; Said Muhammad; Imran Ud Din; Muhammad Yaseen; Hameed Ullah (Environmental Geochemistry and Health, 2020)

Genesis of Manganese Deposits in the Ali Khanzai Block of the Zhob Ophiolite, Pakistan: Inferences from Geochemistry and Mineralogy - Muhammad Ayoub Khan; Muhammad Ishaq Kakar; Thomas Ulrich; Liaqat Ali; Andrew C. Kerr; Khalid Mahmood; Rehanul Haq Siddiqui (Journal of Earth Science, 2020)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Occurrence of heavy metals and pesticide residues in tomato crop: a threat to public health - Muhammad Ishaq; Nighat Sultana; Muhammad Ikram; Amjad Iqbal; Farooq Shah; Muhammad Hamayun; Anwar Hussain (Arabian Journal of Geosciences, 2020)

Eocene carbonate microfacies distribution of the Chorgali Formation, Gali Jagir, Khair-e-Murat Range, Potwar Plateau, Pakistan: approach of reservoir potential using outcrop analogue - Muhammad Awais; Muhammad Hanif; Irfan U. Jan; Muhammad Ishaq; Muhammad Younis Khan (Arabian Journal of Geosciences, 2020)

Efficacy of Alternanthera bettzickiana to Remediate Copper and Cobalt Contaminated Soil Physiological and Biochemical Alterations - Amna Khalid; Mujahid Farid; Muhammad Zubair; Muhmmad Rizwan; Usman Iftikhar; Hafiz Khuzama Ishaq; Sheharyaar Farid; Urousa Latif; Kiran Hina; Shafaqat Ali (International Journal of Environmental Research, 2020)

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Reservoir Inflow Prediction by Ensembling Wavelet and Bootstrap Techniques to Multiple Linear Regression Model - Adnan Bashir; Muhammad Ahmed Shehzad; Ijaz Hussain; Muhammad Ishaq Asif Rehmani; Sajjad Haider Bhatti (Water Resources Management, 2019)

Microfacies and diagenetic studies of the early Eocene Sakesar Limestone, Potwar Plateau, Pakistan: approach of reservoir evaluation using outcrop analogue - Muhammad Ishaq; Irfan U. Jan; Muhammad Hanif; Muhammad Awais (Carbonates and Evaporites, 2019)

Relating petrophysical parameters to petrographic interpretations in carbonates of the Chorgali Formation, Potwar Plateau, Pakistan - Muhammad Awais; Muhammad Hanif; Muhammad Younis Khan; Irfan U. Jan; Muhammad Ishaq (Carbonates and Evaporites, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Petrology and geochemistry of dolerite and lamprophyre sills in Mesozoic successions of Khanozai–Muslim Bagh area, northwestern Pakistan - Din Muhammad; Razzaq Abdul Manan Durrani; Akhtar Muhammad Kassi; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2019)

Pharmacological mechanisms underlying gastroprotective activities of binapthyl diselenide in Wistar rats - Mohammad Ibrahim; Musadiq Ibrahim; Niaz Muhammad; Muhammad Ishaq Ali Shah; Gerlânia de Oliveira Leite; Joao B. T. Rocha (Inflammopharmacology, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Unraveling the inheritance pattern of yield and associated traits in Rapeseed (Brassica napus L.) - Muhammad Ishaq; Sabaz Ali Khan; Raziuddin Razi (Acta Physiologiae Plantarum, 2017)

Detrital mode and whole-rock geochemistry of the Miocene-Pliocene fluvial succession, Pishin Belt, Pakistan: implications on provenance and source area weathering in peripheral foreland basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Muhammad Umar; Mohibullah Mohibullah; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2016)

Geochemistry and petrogenesis of Oligocene volcaniclastic rocks from the Chagai arc: implications for the emplacement of porphyry copper deposits - Rehanul Haq Siddiqui; Muhammad Asif Khan; Muhammad Qasim Jan; Mohammad Ishaq Kakar; Andrew C. Kerr (Arabian Journal of Geosciences, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)